2017
DOI: 10.1111/pce.12992
|View full text |Cite
|
Sign up to set email alerts
|

SUV2, which encodes an ATR‐related cell cycle checkpoint and putative plant ATRIP, is required for aluminium‐dependent root growth inhibition in Arabidopsis

Abstract: A suppressor mutagenesis screen was conducted in order to identify second site mutations that could reverse the extreme hypersensitivity to aluminium (Al) seen for the Arabidopsis mutant, als3-1. From this screen, it was found that a loss-of-function mutation in the previously described SUV2 (SENSITIVE TO UV 2), which encodes a putative plant ATRIP homologue that is a component of the ATR-dependent cell checkpoint response, reversed the als3-1 phenotype. This included prevention of hallmarks associated with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…With this, our short‐term high‐dosage assay complements the long‐term low‐dosage assay as both systems probe different aspects of a plant's response to Al. We postulate that up to threshold concentrations of Al, plant growth is restricted by ATR , ATRIP , SOG1 and TANMEI (Rounds and Larsen, ; Nezames et al ., ; Sjogren et al ., ; Sjogren and Larsen, ), and only at high concentrations of Al, SOG1 and ATM are required for plant recovery and survival as revealed in this study (Figure ). Remarkably, this behaviour resembles mutants in SOG1 itself that were initially identified as suppressors of reduced plant growth following exposure to gamma radiation (Yoshiyama et al ., ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…With this, our short‐term high‐dosage assay complements the long‐term low‐dosage assay as both systems probe different aspects of a plant's response to Al. We postulate that up to threshold concentrations of Al, plant growth is restricted by ATR , ATRIP , SOG1 and TANMEI (Rounds and Larsen, ; Nezames et al ., ; Sjogren et al ., ; Sjogren and Larsen, ), and only at high concentrations of Al, SOG1 and ATM are required for plant recovery and survival as revealed in this study (Figure ). Remarkably, this behaviour resembles mutants in SOG1 itself that were initially identified as suppressors of reduced plant growth following exposure to gamma radiation (Yoshiyama et al ., ).…”
Section: Discussionsupporting
confidence: 64%
“…This is in contrast to a loss‐of‐function mutant for ATM (ataxia telangiectasia mutated), which has little effect on Al tolerance as measured by suppression of als3‐1 . Mutants ATR, ATRIP, SOG1 and TAN/MEI/ALT2 grow even better during long‐term exposure to Al compared with the wild‐type (WT), leaving it unclear whether and, if so, how Al induces DNA damage (Larsen et al ., ; Rounds and Larsen, ; Nezames et al ., ; Sjogren et al ., ; Eekhout et al ., ; Sjogren and Larsen, ).…”
Section: Introductionmentioning
confidence: 98%
“…Decades of study have identified the distal transition zone (DTZ) of the root (1-2 mm from the root tip) as most Al-sensitive (Kollmeier, Felle, & Horst, 2000), and the elongation zone (3-5 mm from the root tip) is regarded as the site of Al-induced inhibition of cellular elongation (Baluška, Volkmann, & Barlow, 2001;Kollmeier, Felle, & Horst, 2000;Sivaguru, Baluska, Volkmann, Felle, & Horst, 1999). The mechanics of Al-mediated root growth inhibition reflects defects in cell wall loosening, cytoskeletal dynamics, or cell cycle arrest (Kopittke, 2016; Kopittke, Menzies, Wang, & Blamey, 2016;Nezames, Sjogren, Barajas, & Larsen, 2012;Sivaguru, Baluska, Volkmann, Felle, & Horst, 1999;Sjogren, Bolaris, & Larsen, 2015;Sjogren & Larsen, 2017). The inhibition of root growth results in reduced uptake of water and nutrients from the soil causing a severe reduction in crop yield and productivity on acidic soil.…”
Section: Introductionmentioning
confidence: 99%
“…Under the interactions between phosphorus and aluminum, the adenosine triphosphate (ATP) and adenylate energy charge (AEC) levels are significantly changed and have an effect on the anaplerotic metabolism of root zone CO 2 [6].Aluminum in soil not only affects plants in special areas, such as pigeonpea, but is also found in the growing environment of many crops, such as rice and tomato [6,[12][13][14]. Additionally, Arabidopsis, as a model plant, has also provided a research basis for Al stress [15][16][17]. Al stress in Arabidopsis, rice, tomato, and pigeonpea has been found to cause aluminum-dependent root growth inhibition [2,6,17].…”
mentioning
confidence: 99%
“…Additionally, Arabidopsis, as a model plant, has also provided a research basis for Al stress [15][16][17]. Al stress in Arabidopsis, rice, tomato, and pigeonpea has been found to cause aluminum-dependent root growth inhibition [2,6,17]. In addition, the transcription factors STOP1 in Arabidopsis and CcSTOP1 in pigeonpea have been proved to play an important role in regulating Al resistance [11,16].…”
mentioning
confidence: 99%